Growth Pattern of the Neo-Aorta after Arterial Switch Operation during Childhood - Cha, Seul Gi (Korean Circ J, 2020)
BACKGROUND AND OBJECTIVES: Neo-aortic root dilatation (ARD) and annular dilatation (AAD) tend to develop after arterial switch operation (ASO). However, the trend of neo-aortic growth has not been well established. This paper aims to identify this trend, its associated factors, and predictors of neo-aortic dilatation after ASO. METHODS: We analyzed the growth trend of the neo-aortic root, annulus, and sinotubular junction (STJ) z-scores using random coefficients model and the risk factors affecting neo-aortic dilatation in 163 patients who underwent ASO from 2006 to 2015. RESULTS: Among 163 patients, 41 had a ventricular septal defect, and 11 had Taussig-Bing (TB) anomaly. The median follow-up duration was 6.61 years. The increased in the neo-aortic root z-score was different between the trapdoor and non-trapdoor coronary artery transfer techniques (0.149/year, p<0.001 vs. 0.311/year, p<0.001). Moreover, the neo-aortic annulus and STJ z-score significantly increased over time after ASO (0.067/year, p<0.001; 0.309/year, p<0.001). Pulmonary artery banding (PAB) was rather a negative affecting factor. The probabilities of freedom from ARD, AAD, and neo-aortic STJ dilatation at 10 years after ASO were 33.4%, 53.9%, and 65.4%. Neo- aortic regurgitation within 1 year was the predictor of ARD, AAD, and neo-aortic STJ dilatation. TB anomaly, PAB, and native pulmonary sinus z-score were other predictors for ARD. CONCLUSION: The growth of neo-aortic root, annulus, and STJ after ASO was greater than somatic growth during childhood. The coronary artery transfer technique affected the growth pattern of the neo-aortic root.